Integrating Science and Technology for Achieving Sustainable Forest Management S.P.Vasudeva - Vasudeva, S.P. (Indian Forester, 2023)
Science and technology can play a significant role in bringing forest sustainability by integrating its various applications into forest management practices. Remote sensing, GIS, GPS, tissue culture, biotechnology, emerging technologies and precision forestry are some of the innovations that can bring such a positive change. These scientific and technological innovations and interventions can and are fastening forest management systems but have to be integrated into forest policy and operational systems to achieve sustainable forest management.